2009
DOI: 10.1111/j.1365-2265.2008.03424.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life changes and clinical outcomes in thyroid cancer patients undergoing radioiodine remnant ablation (RRA) with recombinant human TSH (rhTSH): a randomized controlled study

Abstract: rhTSH preserves QoL of patients undergoing RRA with similar rates of ablation success compared to hypothyrodism. However, there is a wide heterogeneity in the clinical impact of hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 27 publications
4
81
0
4
Order By: Relevance
“…QoL has been extensively evaluated in DTC subjects independently of the cognitive and jobrelated disturbances brought about by changes in circulating thyroid hormone levels for diagnostic and therapeutic purposes (Dow et al, 1997;BotellaCarretero et al, 2003;Golger et al, 2003). More recently, the clinical benefits of the use of recombinant human thyroid-stimulating hormone (TSH), versus thyroid hormone withdrawal, on the preservation of QoL have been demonstrated (Schroeder et al, 2006;Taïeb et al, 2009;Lee et al, 2010). On the other hand, few studies have evaluated QoL in DTC subjects on stabilized levo-thyroxine (L-T4) suppressive treatment a long time after primary therapies.…”
Section: Introductionmentioning
confidence: 99%
“…QoL has been extensively evaluated in DTC subjects independently of the cognitive and jobrelated disturbances brought about by changes in circulating thyroid hormone levels for diagnostic and therapeutic purposes (Dow et al, 1997;BotellaCarretero et al, 2003;Golger et al, 2003). More recently, the clinical benefits of the use of recombinant human thyroid-stimulating hormone (TSH), versus thyroid hormone withdrawal, on the preservation of QoL have been demonstrated (Schroeder et al, 2006;Taïeb et al, 2009;Lee et al, 2010). On the other hand, few studies have evaluated QoL in DTC subjects on stabilized levo-thyroxine (L-T4) suppressive treatment a long time after primary therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The patient is placed back on levothyroxine suppressive therapy, as appropriate, and approximately 1 week after the treatment dose of RAI, a post-therapy WBS is performed to better assess for residual or metastatic disease. Substitution of rhTSH stimulation for TSH stimulation by THW for diagnostic evaluations (shown in Figure 2b and reviewed by Cooper et al (2006) or for thyroid remnant ablation (shown in Figures 1c and 1d), has been published by a number of centers, allowing patients to remain on levothyroxine therapy and avoid the symptoms of hypothyroidism (Robbins et al 2001;Robbins et al 2002b;Barbaro et al 2003;Barbaro et al 2006;Pacini et al 2006a;Pilli et al 2007;Rosario et al 2008;Taieb et al 2008;Tuttle et al 2008). Over the last 3 years, thyrotropin alfa (Thyrogen ® ) has been approved for RAI ablation by the United States Food and Drug Administration (FDA, 2007), in Europe (2005), and in certain Asian (2007) and South American countries (2006).…”
Section: Management Issues In Thyroid Cancer and Use Of Radioiodinementioning
confidence: 99%
“…One of the randomized trials (Taieb et al 2008) compared subjects who all received 3.7 GBq (100 mCi) 131 I after rhTSH preparation or THW. Subjects received levothyroxine therapy for 1 week and then were randomized to either rhTSH (n = 36) or THW (n = 35) preparation for RAI ablation.…”
Section: Rhtsh For Thyroid Remnant Ablationmentioning
confidence: 99%
“…Symptoms described to occur a few weeks after discontinuation of thyroid hormone therapy are changes in peripheral conduction velocity and in the EEG (15). Furthermore, subjective impairments of the quality of life (38)(39)(40) as well as changes in mood (41,42) and decreases in working memory (43) have been reported.…”
Section: Clinical Symptoms During Transient Severe Hypothyroidism Quamentioning
confidence: 99%